Disparities in surgery among patients with intractable epilepsy in a universal health system. (5th January 2016) - Burneo, Jorge G.; Shariff, Salimah Z.; Liu, Kuan; Leonard, Sean; Saposnik, Gustavo; Garg, Amit X.
Abstract : Objective: To assess the use of epilepsy surgery in patients with medically intractable epilepsy in a publicly funded universal health care system. Methods: We performed a population-based retrospective cohort study using linked health care databases for Ontario, Canada, between 2001 and 2010. We identified all patients with medically intractable epilepsy, defined as those with seizures that did not respond to at least 2 adequate trials of seizure medications. We assessed the proportion of patients who had epilepsy surgery within the following 2 years. We further identified the characteristics associated with epilepsy surgery. Results: A total of 10, 661 patients were identified with medically intractable epilepsy (mean age 47 years, 51% male); most (74%) did not have other comorbidities. Within 2 years of being defined as medically intractable, only 124 patients (1.2%) underwent epilepsy surgery. Death occurred in 12% of those with medically intractable epilepsy. Those who underwent the procedure were younger and had fewer comorbidities compared to those who did not. Conclusion: In our setting of publicly funded universal health care, more than 10% of patients died within 2 years of developing medically intractable epilepsy. Epilepsy surgery may be an effective treatment for some patients; however, fewer than 2% of patients who may have benefited from epilepsy surgery received it.